2018
DOI: 10.1111/trf.15101
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mansonella ozzardi among blood donors from highly endemic interior cities of Amazonas state, northern Brazil

Abstract: BACKGROUND In the Brazilian Amazon, the filarial nematode Mansonella ozzardi co‐exists with malaria parasites and thick blood smear microscopy is considered the diagnostic gold standard. Transfusion of M. ozzardi microfilariae does not establish new infections, however microfilariae can survive approximately 2 years in blood‐recipients with unknown risk of pathology. Data on transfusion‐transmitted filariasis are lacking. This study investigated M. ozzardi parasitemias in blood donors from decentralized center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…In a cross‐sectional donor surveillance study of M. ozzardi in the Brazilian Amazon, 28/356 (7·9%) were smear positive and 54/227 (23·8%) were positive by a qualitative nested M. ozzardi NAT [51]. Of the 30 donations, 27 were ultimately deemed to be unusable given seroreactivity for other transfusion‐transmitted infections (TTIs) (mostly HBV, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cross‐sectional donor surveillance study of M. ozzardi in the Brazilian Amazon, 28/356 (7·9%) were smear positive and 54/227 (23·8%) were positive by a qualitative nested M. ozzardi NAT [51]. Of the 30 donations, 27 were ultimately deemed to be unusable given seroreactivity for other transfusion‐transmitted infections (TTIs) (mostly HBV, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…anti‐HBc). For example, in 2019 Abrahim et al reported a 90% interdiction of M. ozzardi positive donors by the concomitant presence of other infectious markers currently used as screening tests; OR = 15·8; CI95%: 4·5–56·1, P < 0·0001] [51].…”
Section: Resultsmentioning
confidence: 99%
“… 17 Even though it appears that contaminated blood is transfused at lower rates than what would be expected from local prevalence levels, it appears that the microfilariae from mansonellosis infections are routinely transfused through-out the developing world. 17 , 18 Although it is known that these transfusions cannot establish chronic infections, the microfilariae are known to be able to persist in the blood for over two years and could thus be contributing to transmission. 18 , 19 At present, the WHO does not provide explicit guidance on how blood stocks contaminated with microfilariae should be treated.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,[14][15][16] Similarly, the chronic nature of mansonellosis infections and the disease´s broad global distribution, means the microfilariae from mansonellosis are a major contaminant of blood stocks in the developing world. 17 Even though it appears that contaminated blood is transfused at lower rates than what would be expected from local prevalence levels, it appears that the microfilariae from mansonellosis infections are routinely transfused through-out the developing world. 17,18 Although it is known that these transfusions cannot establish chronic infections, the microfilariae are known to be able to persist in the blood for over two years and could thus be contributing to transmission.…”
mentioning
confidence: 99%
See 1 more Smart Citation